SEMANTIC AND COMMUNICATIVE TRANSLATION TECHNIQUES IN THE INDONESIAN SUBTITLE TRANSLATIONOF VENOM: THE LAST DANCE - Aprilian Sukmana Adi Putra; Hapsari, Nunuk Tri (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2025)
This study examines the use of semantic and communicative translation techniques in the Indonesian subtitle translation of the film Venom: The Last Dance. Subtitling, as a form of audio-visual translation, requires translators to balance meaning accuracy with readability under technical constraints such as limited space and timing. This research employs a descriptive qualitative method supported by quantitative frequency analysis. The data consist of 30 subtitle units taken from the English and Indonesian subtitle versions of the film. The data were analysed based on Newmark’s (1988) theory of semantic and communicative translation. The findings reveal that both techniques are applied in the subtitle translation, with communicative translation being more dominant (60%) than semantic translation (40%). Semantic translation is primarily used in dialogues that convey narrative significance and emotional depth, ensuring accuracy and fidelity to the source text. In contrast, communicative translation is frequently employed in informal, idiomatic, and humorous expressions to achieve naturalness and immediate comprehension for the target audience. The study concludes that the balanced application of semantic and communicative translation techniques contributes to effective meaning transfer in film subtitling and highlights the importance of adaptive translation strategies in audio-visual translation.